2021
DOI: 10.1186/s13023-021-01878-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, genetic and quality-of-life study of a cohort of adult patients with tuberous sclerosis

Abstract: Background and objective Tuberous sclerosis (TS) is a condition whose manifestations in childhood have been extensively described, but whose presentation in adults is less well known. This study describes the clinical and genetic characteristics, therapeutic management and quality of life of a cohort of adult patients with TS. A comparative study of the characteristics of patients diagnosed in childhood and adulthood is also carried out. Material and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Multiple studies have shown that these patients report a decreased quality of life and require continued monitoring into adulthood. [26][27][28]…”
Section: Psychiatrymentioning
confidence: 99%
“…Multiple studies have shown that these patients report a decreased quality of life and require continued monitoring into adulthood. [26][27][28]…”
Section: Psychiatrymentioning
confidence: 99%
“…4 There are many quality of life (QoL) studies in dermatology literature, yet few address individuals with intellectual or physical disabilities, and none evaluate people with DS. 5 In one study exploring physical conditions that cause pain in patients with DS, pain-induced skin conditions were most frequently reported. 6 For people with disabilities, caregivers may also play an active role in the physical and emotional management of skin disease.…”
Section: Introductionmentioning
confidence: 99%
“…Of patients with DS, 56% experience skin conditions by the time they are young adults 4 . There are many quality of life (QoL) studies in dermatology literature, yet few address individuals with intellectual or physical disabilities, and none evaluate people with DS 5 . In one study exploring physical conditions that cause pain in patients with DS, pain‐induced skin conditions were most frequently reported 6 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is imperative to explore genotype-phenotype correlations to ensure structured management and surveillance are maintained with the variable phenotypic expression seen over time in adult patients with TSC. 10 In this study, we aimed to characterize the phenotypic and molecular characteristics of a Canadian adult TSC population to improve multidisciplinary care and adult patient management.…”
Section: Introductionmentioning
confidence: 99%